2004
DOI: 10.1111/j.1365-2125.2004.02087.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tetracycline on the pharmacokinetics of halofantrine in healthy volunteers

Abstract: AimsTo investigate the effect of tetracycline co-administration on the pharmacokinetics of halofantrine in healthy subjects. MethodsEight healthy males were each given 500 mg single oral doses of halofantrine alone, or with tetracycline (500 mg 12 hourly for 7 days), in a crossover fashion. Blood samples collected at predetermined intervals were analyzed for halofantrine and its major metabolite, desbutylhalofantrine (HFM), using a validated HPLC method. ResultsCo-administration of tetracycline and halofantrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…The results of this study shows that the enzyme activity decreases as the effect of the drug decreases and the peak enzyme activities correlate well the t max of halofantrine as seen in earlier pharmacokinetic studies (Onyeji et al 1998, Bassi PU et al 2004.…”
Section: Discusionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of this study shows that the enzyme activity decreases as the effect of the drug decreases and the peak enzyme activities correlate well the t max of halofantrine as seen in earlier pharmacokinetic studies (Onyeji et al 1998, Bassi PU et al 2004.…”
Section: Discusionsupporting
confidence: 86%
“…These values were also high between the 8-12 hours, which corresponds with the usual peak plasma concentration of halofantrine as seen in literature (Kwabang et al 1984, Milton et al 1985, Watkins et al 1995, Touze JE et al 1996and Bassi et al 2004.…”
Section: Discusionsupporting
confidence: 82%
“…The reason for the altered pharmacokinetics of Hf when co-administered with kolanut is currently unknown. Hf is known to be extensively metabolized by presystemic cytochrome P450 enzymes and, thus, increased plasma concentrations have been observed when the drug is taken with grapefruit juice [15], tetracycline [14] or after pretreatment with ketoconazole [18]. In contrast, decreased plasma concentra- tions were observed when Hf was co-administered with antacid drugs due to adsorptive effects [19].…”
Section: Resultsmentioning
confidence: 92%
“…The pharmacokinetic data obtained by non-compartmental analysis are summarized in Table 2. The data for the oral administration of 500 mg Hf hydrochloride alone are generally in the range reported in the literature [9,[14][15][16][17][18][19]. For example, Bassi et al reported values for c max between 190 and 470 ng/ml and for the AUC (0-336 h) between 15.1 and 42.6 g/ml h [14].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation